Peran Kompetensi Dalam Memediasi Pengaruh Pengembangan Sdm Terhadap Peningkatan Kinerja Pegawai Inspektorat Daerah Kabupaten Konawe Selatan - Maulid, Nur; Abbas, Bakhtiar; Tambunan, Rince; Nur, Muh. (Publikasiku, 2025)
This study aims to find out and analyze (1) The influence of human resource development on the competence of employees of the South Konawe Regency Regional Inspectorate; The determination of the number of samples in this study is by using the census method, namely the number of samples taken from the total population of 60 employees excluding leaders. The data analysis technique in this study uses Partial Least Square (PLS). Based on the results of the study, it can be concluded that (1) Human resource development has a positive and significant effect on the competence of employees at the Regional Inspectorate of South Konawe Regency; (2) Human resource development has a positive and significant effect on employee performance at the Regional Inspectorate of South Konawe Regency; (3) Competence has a positive and significant effect on the performance of employees at the Regional Inspectorate of South Konawe Regency; and (4) Leadership has a positive and significant effect on employee performance through employee competence at the South Konawe Regency Regional Inspectorate.